Особливості мотивації до занять з фізичного виховання курсантів льотних спеціальностей - Гуменний, В. С.; Humennyi, V. S.; ORCID: http://orcid.org/0000-0001-8669-7205; Галата, О. В.; Halata, O. V.; ORCID: http://orcid.org/0000-0001-8081-4730; Ложченко, О. В.; Lozhchenko, O. V.; ORCID: http://orcid.org/0000-0001-5584-6802 (Вісник Херсонського національного технічного університету. - 2021. - № 4(79). - С. 190-195, 2021)
Розглянуто мотивацію до занять фізичними вправами курсантів льотних спеціальностей. Досліджено особливості прояву мотивації до занять фізичною культурою і спортом курсантів. Виявлено зв’язок можливостей самореалізації курсантів в професійному житті та бажанні укріплення здоров’я за допомогою постійних занять фізичними вправами. З’ясовано, що формування мотивації до занять з фізичного виховання є важливою умовою професійної компетентності майбутнього фахівця. Встановлено рейтинг домінуючих мотивів мети відвідування курсантами занять з фізичного виховання. Визначено чинники у структурі мотивації курсантів під час занять різноманітними фізичними вправами. Виділено суттєві відмінності у мотиваційній сфері на різних етапах навчання. Виявлено шляхи підвищення рівня мотивації курсантів, спрямованих на формування у них внутрішньої потреби займатися фізкультурно-оздоровчою діяльністю. Встановлено зв’язок можливостей самореалізації в професійному житті та бажання укріплення здоров’я за допомогою постійних занять фізичними вправами. Виявлено значущість для курсантів усвідомлення впливу рівня фізичної підготовленості для професійної реалізації. Проаналізовано провідні форми занять з фізичного виховання.

Motivation is a special state of a person, aimed at achieving an optimal level of physical fitness and working capacity. The process of developing interest in physical education is not an instant, but a multi-stage process: from the first elementary hygienic knowledge and skills to deep psychophysiological knowledge of the theory and methodology of physical education and intensive sports. The motivation for physical exercises of cadets of flying specialties is considered. The features of manifestation of motivation to physical culture and sports among cadets have been investigated. The connection between the possibilities of self-realization of cadets in professional life and the desire to improve health through constant physical exercises was revealed. Insufficient research of the features of the formation of motivation and the importance of this issue for the effective differentiated organization of physical education among cadets proves the relevance of this issue. It was found that the formation of motivation for physical education classes is an important condition for the professional competence of a future specialist. The rating of the dominant motives of the goal of cadets attending physical education classes has been established. The factors in the structure of cadets' motivation in the classroom with various physical exercises have been determined. Significant differences in the motivational sphere at different stages of training are highlighted. The ways of increasing the level of motivation of cadets, aimed at the formation of their internal need to engage in physical culture and health-improving activities, have been revealed. The connection between the possibilities of self-realization in professional life and the desire to improve health through constant physical exercises has been established. Revealed the importance for cadets of awareness of the influence of the level of physical fitness on professional implementation. The leading forms of physical education classes are analyzed.

Рассмотрена мотивация к занятиям физическими упражнениями курсантов летных специальностей. Исследованы особенности проявления мотивации к занятиям физической культурой и спортом курсантов. Выявлена связь возможностей самореализации курсантов в профессиональной жизни и желании укрепления здоровья с помощью постоянных занятий физическими упражнениями. Установлено, что формирование мотивации к занятиям по физическому воспитанию является важным условием профессиональной компетентности будущего специалиста. Установлен рейтинг доминирующих мотивов цели посещения курсантами занятий по физическому воспитанию. Определены факторы в структуре мотивации курсантов на занятиях различными физическими упражнениями. Выделены существенные отличия в мотивационной сфере на разных этапах обучения. Выявлены пути повышения уровня мотивации курсантов, направленных на формирование у них внутренней потребности заниматься физкультурно-оздоровительной деятельностью. Установлена связь возможностей самореализации в профессиональной жизни и желание укрепления здоровья посредством постоянных занятий физическими упражнениями. Выявлена значимость для курсантов осознания влияния уровня физической подготовленности на профессиональную реализацию. Проанализированы ведущие формы занятий по физическому воспитанию.
Peculiarities of motivation for physical education of flight cadets
Особенности мотивации к занятиям по физическому воспитанию курсантов летных специальностей
Гуменний, В. С. Особливості мотивації до занять з фізичного виховання курсантів льотних спеціальностей / В.С. Гуменний, О.В. Галата, О.В. Ложченко // Вісник Херсонського національного технічного університету. - 2021. - № 4(79). - С. 190-195. - DOI: https://doi.org/10.35546/kntu2078-4481.2021.4.22.
Keywords: Фізична культура. Спорт. Physical Education. Sport. Физическая культура. Спорт; Наукові публікації. Scientific publications. Научные публикации; Психологія. Рsychology. Психология; Освіта. Педагогіка. Education. Pedagogy. Образование. Педагогика; Україна. Ukraine. Украина; мотивація; motivation; мотивация; фізичне виховання; physical education; физическое воспитание; навчальний процес; learning process; учебный процесс; курсанти; cadets; курсанты; курсанти льотних спеціальностей; фізична підготовленість; physical fitness; физическая подготовленность; фізичні вправи; physical exercises; физические упражнения